Rheumatic pain management: molecular aspects - E. V. Chetina; E. P. Sharapova (Современная ревматология, 2020)
Rheumatic diseases (RDs), including osteoarthritis and rheumatoid arthritis, are non-infectious slowly progressive incurable inflammatory diseases that lead to prolonged disability due to damage to the musculoskeletal system. Pain is a dominant symptom at any stage of these diseases, is directly related to joint functioning, and determines the quality of life in patients. Moreover, despite the significant successes of studying the role of inflammation and regulation of autoimmune processes, the pathogenetic mechanisms for the development and maintenance of pain in RDs are little investigated. The nociceptive mechanisms due to inflammation and/or joint structural impairment are involved in the development of rheumatic pain. In addition, the latter is also associated with impaired signaling in the nervous system and with psychological problems in patients.At the present stage, pain treatment includes non-pharmacological interventions, as well as the use of certain pharmacological agents, in particular opioids and narcotic drugs. However, despite significant successes in the design of drugs that relieve pain, at present, a significant proportion of patients with RDs still experience pain after therapy. When designing novel drugs for the treatment of pain, it is necessary to take into account the molecular mechanisms of its development in RDs. This review considers the features of the manifestations of pain, its molecular markers and mechanisms at different stages of the disease in patients with the two most common RDs, such as rheumatoid arthritis and osteoarthritis.